Dalton's justice - Compton, Ralph; Stowers, Carlton (Gunfighter series., 2021)
"It's been ten years since the worst day of Ben Dalton's life. After four grinding years of war, the Confederate veteran returned to his hometown of Aberdeen, Texas, to find that Mandy, the girl he loved, had run off with his best friend, John Rawlings. Dalton recovered from the loss and spent the next decade settling down to life as the town's marshal. That quiet life is shattered with the arrival of one stunning telegram. Mandy begs her old friend to come to Fort Worth, where her lawyer husband has been arrested for murder. Without a second's hesitation, Dalton heads to the big city, where he will discover that the forces who want Rawlings convicted won't hesitate to commit a second murder to silence a visiting lawman."--